Structural evolution of cobalt for the production of long-chain paraffins by CO2 hydrogenation - Jo, Heuntae; Chun, Hee Joon; Sugiarto, Junjung Rohmat; Khan, Muhammad Kashif; Irshad, Muhammad; Yoon, Wonjoong; Kim, Seok Ki; Kim, Jaehoon (Applied Catalysis B: Environmental, 2024)
A new role of alkali metals in the direct hydrogenation of CO2 to C5+ species over Co catalysts was proposed. During the CO2 hydrogenation, Na-promotion encouraged a new structural evolution (i.e., a thin oxygen vacancy (Ov)-rich Co3O4/Co2C shell and a Co0 core). This facilitated the migration of CHxO and CO species produced at the shell to the adjacent Co2C shell and Co0 core, where they undergo further chain growth. In contrast, Li- and K-promotion resulted in the generation of a thick and Ov-poor Co3O4 shell without Co2C, while in the absence of alkali metal promotion, Co0 was exposed as the outmost surface; in both the cases, methanation dominated. The ability of Na-promotion to remove –OH* from the Co surface helped maintain the thickness and valance state of the Co oxide shell. Thus, the Na-promotion developed the chain growth and CO producing core–shell structure, rather than any electronic promotional effects.
Keywords: Alkali; Alkali-metal promotion; Chain growth; Co catalysts; CO2 hydrogenation; K promotion; Long chains; Promoter; Structural evolution; Valance state; Alkali; CO2 Hydrogenation; Cobalt; Mechanism; Promoter